MATERIAL LIVING CONDITIONS AND ECONOMIC SECURITY OF THE POPULATION IN THE REPUBLIC OF NORTH MACEDONIA - Vladimir Petkovski, Iskra Stanceva Gigov (Institute of Economics-Skopje, University “Ss. Cyril and Methodius” in Skopje, Republic of North Macedonia, 2022)
In the past few years, as the world and conditions we live in are constantly changing, it demands that the measurements for quality of life change accordingly. Measurements of quality of life can not be just a canonical representation of the economic development of countries and their populations. They should, in fact, encompass the whole of life, namely the objective and subjective perception of the individual about the quality of life. The economic measure of GDP for measuring the quality of life can not estimate the quality of life, therefore we move to a more comprehensive range of indicators when it comes to measuring the quality of life of the citizens in a country, more specifically the Republic of North Macedonia. This research paper looks to present the material living conditions and economic security of the people of North Macedonia as a part of quality of life indicators proposed by Eurostat. The statistics’ indications show that the Republic of North Macedonia regarding the material living conditions is at a relatively adverse level. There is still a large percentage of people living in severe material conditions or at the poverty threshold and the pandemic is causing that value to rise. . Furthermore, most analyses indicate that the population live in conditions of economic insecurity, and the pandemic additionally jeopardized and influenced its increase. Therefore, social economic measures and changes are needed, which can improve the material conditions for the life of the population, reduce the percentage of those living on the margins and increase the economic security of the population.
Keywords: Material living conditions, Poverty, Economic security, Republic of North Macedonia